2004
DOI: 10.5194/nhess-4-647-2004
|View full text |Cite
|
Sign up to set email alerts
|

Results of subionospheric radio LF monitoring prior to the Tokachi (M=8, Hokkaido, 25 September 2003) earthquake

Abstract: Abstract.Results of simultaneous LF subionospheric monitoring over two different propagation paths prior to the very strong Tokachi earthquake (near the east coast of Hokkaido Island, 25 September 2003) of magnitude 8.3 are presented firstly. Nighttime amplitude fluctuations of the Japanese Time Standard Transmitter (JG2AS, 40 kHz) signal received at Moshiri (Japan, 142 • E, 44 • N) and at PetropavlovskKamchatski (Russia, 158 • E, 53 • N) were analyzed. As a possible precursory signature we observed synchronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 15 publications
(21 reference statements)
0
34
0
Order By: Relevance
“…Our former case studies include the (1) Kobe EQ (17 January 1995) (Hayakawa et al 1996), (2) Tokachi-oki EQ (25 September 2003) (Shvets et al 2004;Cervone et al 2006), (3) Niigata-chuetsu EQ (23 October 2004) Yamauchi et al 2007), (4) the 1999 Chi-chi EQ in Taiwan (Hayakawa et al 2005) and, (5) the 2004 Sumatra EQ (Horie et al 2007a, b). The details of seismogenic effects for these EQs are summarized in our review by Hayakawa (2009c).…”
Section: Introductionmentioning
confidence: 99%
“…Our former case studies include the (1) Kobe EQ (17 January 1995) (Hayakawa et al 1996), (2) Tokachi-oki EQ (25 September 2003) (Shvets et al 2004;Cervone et al 2006), (3) Niigata-chuetsu EQ (23 October 2004) Yamauchi et al 2007), (4) the 1999 Chi-chi EQ in Taiwan (Hayakawa et al 2005) and, (5) the 2004 Sumatra EQ (Horie et al 2007a, b). The details of seismogenic effects for these EQs are summarized in our review by Hayakawa (2009c).…”
Section: Introductionmentioning
confidence: 99%
“…There have been so many case studies on subionospheric VLF/LF propagation anomalies; e.g., Kobe EQ (Hayakawa et al, 1996), Tokachi-oki EQ (Shvets et al, 2004), Niigata-chuetsu EQ , Indonesia-Sumatra EQ (Horie et al, 2007), etc. In addition to these case studies, statistical studies on the correlation of ionospheric perturbations with EQs are highly required.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these signals can propagate into the ionosphere and generate variations of the ionosphere parameters such as critical plasma frequency f 0 F2, virtual height h m F2 and of the ionospheric total electron content (TEC). The mechanism of appearance of the ionospheric anomalies includes direct coupling between the Earth's surface and the lower ionosphere through electric current (e.g., Pulinets et al, 2000), and triggering of atmospheric gravity waves by gas releases or thermal anomalies (Shalimov, 1992a(Shalimov, , 1992bGokhberg et al, 1994Gokhberg et al, , 1996Pertsev and Shalimov, 1996;Molchanov and Hayakawa, 2001; Shvets et al, 2004). Thereby, at present, pre-seismic ionosphere anomalies seem to be well analyzed, and discussed in numerous papers (e.g., Pulinets, 1998 Wenchuan Earthquake (M7.9) by using global ionosphere maps (GIM), and have found that TEC above the forthcoming epicenter anomalously decreased in the afternoon period four to six days before the earthquake, and in the late evening period three days before the earthquake.…”
Section: Introductionmentioning
confidence: 99%